Critical factors of farmers's participation in kenaf cultivation: Malaysian context - Othman, Mohd Shahwahid; Amir Mustafa, Amira Mas Ayu; Kamaruddin, Norfaryanti (Academic Journals, 2012)
The Malaysian government has given support and priority to Kenaf as a new national commodity. However, the progress in Kenaf cultivation has not met the expectation of the government. The main objective of this study is to determine the critical factors influencing the limited farmer participations in Kenaf cultivation. Data were collected through interviews using a structured questionnaire that is designed to map out the farmers perspective with respect to this matter. Factor analysis indicates that there are six significant influential factors including inadequate economic potentials in Kenaf cultivation, strategicness of tobacco cultivation, grievances over Kenaf cultivation, farmers’ perspectives in changing crop cultivation, challenges in market assurances and inadequate Kenaf cultivation campaign and promotion to farmers. The government has to take note and resolve these critical factors to encourage Kenaf cultivation by farmers.